Síntese, caracterização e aplicação de óxidos mistos ce1-x fex o2-õ para fotodegradação de compostos nitroaromáticos de água residuária da indústria de explosivos - Nava, Mariana Riboli (2019)
The present work aimed to synthesize mixed cerium and iron oxides, with different iron contents, characterize them and evaluate the photocatalytic efficiency in the degradation of nitroaromatic compounds constituting effluent from the explosives industry, evaluate the physicochemical aspects and effluent toxicity before and after the treatments. The characterization tests proved the introduction of iron in the CeO2structure.Experimental design allowed us to assess that ultraviolet radiation was more efficient in activating catalysts than visible radiation, and suggested that higherconcentration (7.5 gL-1), lower iron content in the catalyst structure (CF10) and lower pH value (3.0) favored the degradation mechanism of nitroaromatic compounds. The photocatalytic treatment during 360 minutes of reaction promoted 96% degradation in the best experimental conditions defined by the factorial design, proving effective for mineralization of 97% of the organic compounds.Acute ecotoxicity assays based onArtemia and Lemnas bioassays revealed that both bioindicators showed enhanced sensitivity to untreated effluent.The prolongation of the reaction time of 360 minutes increased the degradation of toxic compounds present in the effluent, reducing toxicity for both Artemia and Lemnas. It can be concluded that the treatment was efficient and capable of significantly reducing the concentration of nitroaromatic compounds and toxicity.